2018
DOI: 10.1177/0022022118787042
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Cross-Cultural Comparability of Self-Reports Using the Overclaiming Technique: An Analysis of Accuracy and Exaggeration in 64 Cultures

Abstract: The overclaiming technique (OCT) is a novel way of measuring how socially desirable responding influences survey responses. It has the potential to enhance the cross-cultural comparability of survey data. It allows the identification of respondents’ knowledge accuracy and exaggeration by comparing their assessments of familiarity with existing and nonexisting concepts in a particular field of knowledge. We aim to compare the response patterns of countries and world regions based on their OCT accuracy and exagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
1
22
0
3
Order By: Relevance
“…However, there are cross-cultural differences in accurately estimating and overestimating one’s knowledge. For example, Vonkova et al [ 99 ] found that students in East Asia estimate their knowledge highly accurately, but students in Southern and Central America do not. Furthermore, students in Southern Europe tend to exaggerate their knowledge more than those in Western Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are cross-cultural differences in accurately estimating and overestimating one’s knowledge. For example, Vonkova et al [ 99 ] found that students in East Asia estimate their knowledge highly accurately, but students in Southern and Central America do not. Furthermore, students in Southern Europe tend to exaggerate their knowledge more than those in Western Europe.…”
Section: Discussionmentioning
confidence: 99%
“…However, there seems to be no consistent pattern in terms of accurately estimating and overestimating knowledge across the Middle East. Since Saudi Arabia is not included in Vonkova et al’s study [ 99 ], it is not clear how students with this particular cultural background would fare in terms of accuracy and exaggeration of estimated knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were obtained from studies targeting design-based correction procedures applied in the 2012 Programme for International Student Assessment (PISA) data. In these studies, design-based corrections did not always result in scalar invariance (e.g., Marksteiner et al, 2019), and the relations with the criterion (i.e., achievement) differed between uncorrected and corrected scores (e.g., Vonkova, Papajoanu, et al, 2018). One limitation of this work is that each correction procedure was independently assessed, with the assumption that such corrections operate on data from all respondents to the same extent.…”
mentioning
confidence: 81%
“…Applications of the aforementioned procedures are common, and their effects can result in changes in psychometric properties of target constructs, criterion and predictive validity of scales (i.e., structural relations) and mean comparisons across groups (e.g., Bartram, 1996; Vonkova, Papajoanu, et al, 2018). We argue that correction effects on structural relations and mean comparisons should be built on sound psychometric properties of corrected scores.…”
Section: Correction Procedures For Enhancing Data Comparabilitymentioning
confidence: 99%
See 1 more Smart Citation